2017
DOI: 10.1016/j.jsbmb.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Butyric acid regulates progesterone and estradiol secretion via cAMP signaling pathway in porcine granulosa cells

Abstract: Butyric acid (BA), one of the short chain fatty acids (SCFAs), has positive actions on the metabolism, inflammation, etc. However, whether it influences the reproductive physiology and if so the detail mechanism involved has not yet been determined. In this study, the porcine granulosa cells (PGCs) were treated with gradient concentrations of BA. After 24h culture, 0.05mM BA significantly stimulated the progesterone (P) secretion (P<0.05), 5mM and 10mM BA significantly inhibited the P secretion (P<0.05). Simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…90 The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor-alpha-mediated signaling. 91,92 These result implied that the SCFAs potentially play an important role in DEHP-induced female reproductive toxicology. Overall, the reduction in the SCFA levels after DEHP exposure may be due to gut bacterial dysbiosis and alterations in gut permeability.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…90 The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor-alpha-mediated signaling. 91,92 These result implied that the SCFAs potentially play an important role in DEHP-induced female reproductive toxicology. Overall, the reduction in the SCFA levels after DEHP exposure may be due to gut bacterial dysbiosis and alterations in gut permeability.…”
Section: Discussionmentioning
confidence: 84%
“…A study showed the changes of fecal microbiota composition and metabolites are related to the plasma reproductive hormones during pregnant and lactating stages in Bama mini pigs model 90 . The SCFA not only regulates the estradiol secretion but also participates in endogenous estrogen receptor‐alpha‐mediated signaling 91,92 . These result implied that the SCFAs potentially play an important role in DEHP‐induced female reproductive toxicology.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of gut microbiota, as well as their metabolites, such as short-chain fatty acids (SCFAs), has been reported to play a role in the regulation of the testis‒pituitary axis [63] by disrupting steroid hormone synthesis [64]. It has been verified in cells that butyrate acid may increase the level of estradiol [65]. Accordingly, several butyrate-producing genera were significantly enriched in the DEP-H group, including Alloprevotella [66] and Intestinimonas [67] (Figure 5C, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that butyrate can suppress early embryo loss through improving phospholipid metabolism and enhancing ovarian progesterone synthesis 12 . In vitro cultured granulosa cells of rats and pigs also suggest the improvements of progesterone and estradiol synthesis by butyrate 10,12 . However, the underlying molecular mechanism for this improvement is largely unknown.…”
Section: Introductionmentioning
confidence: 89%
“…SR‐BI/CD36 drives the transport of extracellular cholesterol into mitochondria for steroidogenesis 9 . In clinical practice, dietary fats have been reported to influence the levels of steroid hormones, including progesterone, estradiol, and testosterone, in mammals and rodents 10‐12 . We and others have found that maternal dietary butyrate supply during pregnancy leads to improvement of litter size and embryo implantation in rats 12,13 .…”
Section: Introductionmentioning
confidence: 97%